Analysis of Mathematical Logic Intelligence of Children Aged 4-5 Years at KB Scholar Bapangan in Terms of the Application of Outing Class Learning Methods - Utami, Nurulita Tri; Zulfahmi, Muhammad Nofan (AS-SABIQUN, 2024)
This study focuses on an in-depth exploration of the influence of the "Outing Class" learning method on the development of logical mathematical intelligence in children aged 4-5 years at KB Cendekia Bapangan. This research uses a qualitative descriptive approach with case studies as the method, and data is collected through participatory observation, interviews, and document analysis. The findings of this study show that the Outing Class method is very effective in enriching children's logical mathematical intelligence. Teachers use a variety of practical activities, such as planting, to teach the concept of causation and the basics of mathematics. Although there are obstacles such as lack of discipline of children during outdoor activities, teachers manage to overcome this with the right approach. In addition, the annual program has been designed to ensure the long-term sustainability of Outing Class benefits . Thus, the Outing Class method is proven to make a positive contribution to the development of early childhood mathematical logic intelligence.